Unravelling CO2 transfer through cork stoppers for Champagne and sparkling wines. (March 2021) - Crouvisier Urion, Kevin; Bellat, Jean-Pierre; Liger-Belair, Gérard; Gougeon, Régis D.; Karbowiak, Thomas
Graphical abstract: Highlights: The mechanism of gas transfer through the agglomerated cork stopper is elucidated. Gas transfer depends on particle size and adhesive content. Compression has a very strong effect on gas transfer. Surface diffusion through the adhesive network is the limiting step for gas transfer. Abstract: The diffusion of CO2 through macro- and micro-agglomerated cork stoppers for sparkling wine was studied by a manometric technique. The effective diffusion coefficients for each part of the stopper (cork body, cork disc and adhesives) were determined for the first time. The results show that a small particle size along with a high adhesive content and level of compression favor the gas barrier properties of the cork stopper. Although the cork discs placed at one end of the stopper present no resistance to gas transfer, the adhesive film between them constitutes a high barrier to gas transfer. The mechanism that controls the gas transfer is the solution-diffusion process through the polymeric chains of the adhesive. Although the aging of the cork stopper and the gas transfer at the glass/stopper interface were not considered, results clearly showed that the cork stoppers studied were capable of maintaining a CO2 concentration in the bottle that is sufficient for conserving a good effervescence of sparkling wines over several years.